2015
DOI: 10.1144/jgs2014-067
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing diapirs from inflated plutons: an integrated rock magnetic fabric and structural study on the Roundstone Pluton, western Ireland

Abstract: Granitoid plutons account for much of the continental crust and are critical in the generation of several economic resources. Despite over a century of research, the fundamental process by which large felsic bodies intrude remains controversial. Two contrasting models persist: (1) mass ascent and subsequent cooling of magma (diapirism); (2) sheet ascent and subsequent emplacement (laccoliths). The latter hypothesis is different from the former as distinct ascent and emplacement processes must occur and be iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 148 publications
(168 reference statements)
0
20
0
Order By: Relevance
“…Several different analytical methods have been used to decipher the mineral fabric in magmatic intrusions, e.g., the use of a petrographic microscope equipped with a universal stage (e.g., Brothers, 1964;Žák et al, 2005), neutron diffraction goniometry (Silva et al, 2014), electron backscatter diffraction (EBSD) (Holness et al, 2012), and anisotropy of magnetic susceptibility (AMS) (Knight and Walker, 1988;Geoffroy et al, 2002;Žák et al, 2005;de Saint-Blanquat et al, 2006;Stevenson et al, 2007;Horsman et al, 2009;Eriksson et al, 2011;Payacán et al, 2014;Roni et al, 2014;McCarthy et al, 2015). Crystallographic preferred orientation (CPO) and shape preferred orientation (SPO) are often analyzed with oriented thin sections and require distinct crystal boundaries (e.g., Benn and Allard, 1989;Paterson et al, 1998;Geoffroy et al, 2002;Horsman et al, 2009;Payacán et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several different analytical methods have been used to decipher the mineral fabric in magmatic intrusions, e.g., the use of a petrographic microscope equipped with a universal stage (e.g., Brothers, 1964;Žák et al, 2005), neutron diffraction goniometry (Silva et al, 2014), electron backscatter diffraction (EBSD) (Holness et al, 2012), and anisotropy of magnetic susceptibility (AMS) (Knight and Walker, 1988;Geoffroy et al, 2002;Žák et al, 2005;de Saint-Blanquat et al, 2006;Stevenson et al, 2007;Horsman et al, 2009;Eriksson et al, 2011;Payacán et al, 2014;Roni et al, 2014;McCarthy et al, 2015). Crystallographic preferred orientation (CPO) and shape preferred orientation (SPO) are often analyzed with oriented thin sections and require distinct crystal boundaries (e.g., Benn and Allard, 1989;Paterson et al, 1998;Geoffroy et al, 2002;Horsman et al, 2009;Payacán et al, 2014).…”
mentioning
confidence: 99%
“…In viscous magma intrusions, the emplacement-related magmatic fabrics are commonly concentric and reflect the shape of the magma body (e.g., de Saint-Blanquat et al, 2006;Stevenson et al, 2007;Payacán et al, 2014;McCarthy et al, 2015). Therefore, the magmatic fabrics have been interpreted as due to divergent flow in the magma body or by compaction against the magma body roof and wall (e.g., Paterson et al, 1998;Buisson and Merle, 2004).…”
mentioning
confidence: 99%
“…Circumferential magmatic to submagmatic fabrics in shallow plutons elsewhere have been interpreted to record concentric expansion of plutons, diapiric magma ascent, laccolithic growth, or a helical magma flow in a posttectonic stress regime (e.g., Machek et al, 2019;McCarthy et al, 2015;Paterson & Vernon, 1995;Trubač et al, 2009;Žák et al, 2011). The domainal nature of the Alamosa River monzonite, however, best corresponds to a convective flow pattern (Gutiérrez et al, 2013;Payacán et al, 2014).…”
Section: Complex Multipulsed Emplacement Of the Alamosa River Plutonmentioning
confidence: 99%
“…Due to the lack of outcrops and observable structural record in the vicinity of the pluton, it is impossible to speculate about the mechanism of space creation for the CCG. McCarthy et al () suggested that the distinction between the contrasting emplacement mechanisms (e.g., ballooning vs. diapiric) for the CEPs is possible through detailed investigation of the internal structure using high‐resolution AMS that can distinguish the processes of magma ascent and emplacement (Jacques & Reavy, ). However, in regard to the scenario presented for the CCG pluton, the intrusion‐related fabrics are recorded only in the central trondhjemite.…”
Section: Discussionmentioning
confidence: 99%
“…This compaction is attributed to the late intrusion of trondhjemite magma that pushed the earlier emplaced portions from the center to the margins of the pluton and culminated in coeval formation of the final submagmatic and subsolidus fabric in the porphyritic and fine-grained granodiorite (Figures 9c and 9d). The change from magmatic to subsolidus fabric is a typical feature of many CEPs (e.g., Dietl & Koyi, 2002;He et al, 2009;Johnson et al, 2003;McCarthy et al, 2015;Molyneux & Hutton, 2000;Paterson & Vernon, 1995;Žák et al, 2011).…”
Section: Growth Of the Concentrically Zoned Plutonmentioning
confidence: 99%